8.7k views
1 vote
Given that (X+3) is a factor of the expression x^3 + 4x^2 + px + 3 , find the value of p. Hence, solve the equation x^3 + 4x^2 + px + 3=0, expressing the complex number in the form a + bi​

1 Answer

3 votes

Answer:


p=4


x=(-1)/(2) \pm (√(3))/(2)i

Explanation:

We are given (x+3) is a factor of
x^3+4x^2+px+3, which means if were to plug in -3, the result is 0.

Let's write that down:


(-3)^3+4(-3)^2+p(-3)+3=0


-27+36-3p+3=0


9-3p+3=0


9+3-3p=0


12-3p=0


12=3p


p=4

So the cubic equation is actually
x^3+4x^2+4x+3=0 that they wish we solve for
x.

To find another factor of the given cubic expression on the left, I'm going to use synthetic division with that polynomial and (x+3) where (x+3) is divisor. Since (x+3) is the divisor, -3 will be on the outside like so:

-3 | 1 4 4 3

| -3 -3 -3

---------------------

1 1 1 0

So the other factor of
x^3+4x^2+4x+3 is
(x^2+x+1).

We must solve
x^2+x+1=0.

Compare this to
ax^2+bx+c=0.

We have
a=1,b=1, \text{ and } c=1.

The quadratic formula is


x=(-b \pm √(b^2-4ac))/(2a).

Plug in the numbers we have for
a,b, \text{ and } c.


x=(-1 \pm √(1^2-4(1)(1)))/(2(1)).

Simplify inside the square root while also performing the one operation on bottom:


x=(-1 \pm √(1-4))/(2)


x=(-1 \pm √(-3))/(2)

Now our answer will include an imaginary part because of that sqrt(negative number).

The imaginary unit is
i=√(-1).

So our final answer is:


x=(-1)/(2) \pm (√(3))/(2)i

User Ahmad Muzakki
by
4.2k points